Study of the Porosity of Certain pharmaceutical Tablets using Mercury Intrusion Porosimeter - Baghdad Science Journal (Baghdad Science Journal, 2009)
Porosity and pore structure are important characteristics of pharmaceutical tablets, since they influence the physical properties, such as mechanical strength, density and disintegration time. This paper is an attempt to investigate the pore structure of four different paracetamol tablets based on mercury porosimetry. The intrusion volumes of mercury were used to calculate the pore diameter, pore volume and pore size distribution. The result obtained indicate that the variation of the pore volume in the tablets followed the sequence:- S.D.I. Iraq? Pharmacare,Dubai-U.A.E.? Bron and Burk(UK) London?Lark Laboratories(India), while the variation of surface area followed the sequence:- S.D.I. Iraq? Lark Laboratories(India)? Pharmacare,Dubai-U.A.E. ? Bron and Burk(UK) London